Efecto de gremios de hongos micorrícicos arbusculares aislados de un ambiente desértico sobre el crecimiento de frijol Phaseolus vulgaris bajo una condición de déficit hídrico (2014)
ABSTRACT: Arbustuve mycorrhizal fungi (HMA) increase the ability of plants to resist or tolerate stressful conditions such as those caused by nutrient deficiency, attack by pathogens, chemical contaminants, and water deficit. However, these fungi have different effects on plants that are regulated y the plant, the fungus and environmental conditions, so that although there is no specificity between symbionts fungi is essential to insure a beneficial symbiosis. In this study, we selected five sampling sites located in the upper Guajira of Colombian in the municipalities of Riocha and Maicao, considering the plant community and physical characteristics of the soils. The fungi were multiplied in sterile soil and a mixture of plant species (Allium cepa, Calendula officials, Lolium perenne y Phaseolus vulgaris) were used as plant traps. After 10 weeks of multiplication, two guilds were selected based on the content of propagules. We evaluated 6 treatments with 7 replicates per treatment: two guilds of HMA (G 3 and G 4) and a control without fungus (C) and two moisture conditions [water overwhelmed (AH) and without water burden (SAH)]. The effects of the guilds and the moisture condition on plant height, leaf area, leaf number, root dry weight, stem diameter of bean plants (Phaseolus vulgaris) and the percentage of mycorrhizal colonization (hyphae, vesicles, and arbuscules) were evaluated. When plants were maintained without hydric stress, the best guild was G 3 and for plants under hydric stress the best guild was G 4. Mycorrhizal fungi native to desert climate may be effective alternatives for use with crops exposed to drought conditions.